Differentiation of pupillary signals using statistical and functional analysis - Babiker, A. (IEEE Computer Society, 2014)
Emotion recognition nowadays plays vital role in human-computer reaction. Different approaches and methods were applied to recognize accurately individual's emotions. However, pupil diameter (PD) is one of the well-known and reliable approaches in identifying emotions. It is controlled by Automatic Nervous System (ANS) and is easy to detect. The goal of this paper is to identify the difference in PD due to individual's positive and negative emotional states. The paper introduces an experiment conducted to measure dilation in pupil diameter using eye-tracking system during positive and negative emotions. Thirty participants were involved in this experiment and the initial results suggested differences in pupil dilation during negative and positive stimulation at the last seconds of a played sound. It shows more sustained, stable and longer dilation in high arousal negative stimuli. It also discussed functional analysis that is proven to be a useful tool in expressing pupil dilation differences. Â© 2014 IEEE.